Abdominopelvic actinomycosis in three different locations with invasion of the abdominal wall and ureteric obstruction: An uncommon presentation. (2015) - Galata, Christian L.; Vogelmann, Roger; Gaiser, Timo; Post, Stefan; Horisberger, Karoline
Highlights: We present an uncommon case of extended abdominoplevic actinomycosis. The patient underwent successful surgical and subsequent long-term antibiotic therapy. The possibility of a malignant process required radical resection. Actinomycisis should be considered when a pelvic mass is associated with use of an intrauterine device. Abstract: Introduction: Actinomycosis is a rare chronic infectious disease caused by Gram-positive anaerobic bacteria that normally colonize the bronchial system and gastrointestinal tract in humans. The most common diseases associated with actinomycosis are orocervicofacial, thoracic and abdominal infections involving Actinomyces israelii. Due to its rarity, its various clinical presentations and often-infiltrative characteristics in radiological imaging, it can easily be mistaken for other clinical conditions, including malignancy. Presentation of case: We present an uncommon case of extended abdominopelvic actinomycosis with infiltrative lesions in multiple locations, including an abscess in the abdominal wall and ureteric obstruction, which underwent successful surgical and subsequent long-term antibiotic therapy. Discussion: To our knowledge, such a combination of different sites of manifestation has not yet been reported for actinomycosis in the presence of an IUD. Possible differential diagnoses included diverticulitis with covered perforation, pelvic inflammatory disease, tuberculosis and inflammatory bowel disease. The possibility of a malignant process required radical resection. As in most cases of actinomycosis, diagnosis could not be established with certainty until postoperative pathology investigation. Conclusion: A rare actinomyceal infection should be considered in patients with a non-specific pelvic mass and atypical abdominal presentations, especially if a previous history of IUD usage is known.